1970
DOI: 10.2337/diab.19.11.842
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Insulin and Glucose Responses of Healthy Subjects to Varying Glucose Loads During Three-hour Oral Glucose Tolerance Tests

Abstract: The plasma glucose and plasma immunoreactive insulin concentrations of twelve healthy, nonobese, adult subjects were compared following administration of oral glucose loads of 50, 75 and 100 gm., and 1.75 gm./kg. body weight. The time -of occurrence and the magnitude of maximal plasma glucose and insulin concentrations were unaffected by the 25 gm. increases in glucose load. The 50 gm. glucose load gave the smallest plasma glucose response during the three-hour tests and this response was statistically disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

1971
1971
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 3 publications
4
33
0
Order By: Relevance
“…It is reported that various amounts of carbohydrate load (50-100 g, 30 g/square meter of body surface) does not influence the peak blood glucose levels at 1 h, but slightly lower 2 h glucose values were seen with a load of 50 g or 30 g square meter of body surface compared with 75 or 100 g loading [7,8]. Therefore, the time delay for the ingestion of the latter half of the cookie does not significantly influence the glucose level at peak and 2 hr.…”
Section: Cookie Test and Measurementmentioning
confidence: 99%
“…It is reported that various amounts of carbohydrate load (50-100 g, 30 g/square meter of body surface) does not influence the peak blood glucose levels at 1 h, but slightly lower 2 h glucose values were seen with a load of 50 g or 30 g square meter of body surface compared with 75 or 100 g loading [7,8]. Therefore, the time delay for the ingestion of the latter half of the cookie does not significantly influence the glucose level at peak and 2 hr.…”
Section: Cookie Test and Measurementmentioning
confidence: 99%
“…Our first two patients had portacaval transposition; cnd-to-side portacaval shunt was used for the last 5. In Cases 3,4,6, and 7 parenteral hyperalimentation as described by Folkman et al,9 was used for 29, 13, 6, and 7 days. When performing the end-to-side portacaval shunts, all tributaries of the portal vein were ligated and divided from just above the pancreas to the division into the right and left portal branches.…”
Section: Methodsmentioning
confidence: 99%
“…Patients 3,4, and 5 had plasma somatotropin determinations after portal diversion. The same investigations were performed for an unoperated Sibling of patient 4 for whom portacaval shunt is planned.…”
Section: Metabolic Effectsmentioning
confidence: 99%
“…To estimate the number of subjects to be included for valid interpretation of the results, available data on healthy volunteers were used [ 9]. Using a power of 95%, giving a two-sided significance level of 0.05, and the formula described by Fleiss [ 10], the required number of healthy volunteers to demonstrate relative to placebo a decrease of the area under the curve of the post-peak blood values of 10% after miglitol, as found by Joubert et al [ 3,4 ], was calculated to be 12.…”
Section: Discussionmentioning
confidence: 99%